INTRODUKSI PASANGAN CMA DAN RHIZOBIA INDIGENOUS UNTUK PENINGKATAN PERTUMBUHAN DAN HASIL KEDELAI DI ULTISOL BENGKULU - Yudhi H. Bertham; C. Kusmana; Y. Setiadi; I. Mansur; D. Sopandie (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2005)
In response to the need of shade tolerant of soybean varieties for agroforestry, we conduct a research to find soybean variety which gave high response to AMF (arbuscular mycorrhizal fungus) and strain of rhizobia inoculation. Research was conducted in a greenhouse by three factor of randomized completely design and replicated three times using top soil of Ultisol from Bengkulu province. First factor was soybean varieties namely Wilis, Pangrango and Ceneng. Second factor was AMF inoculation with Acaulospora sp, Gigaspora margarita, Glomus etunicatum and Glomus manihotis. Third factor was rhizobia inoculation with TEKR 6.29 and KLKR 5.31 strains. Selected AMF and rhizobia isolates was obtained from previous research and taken from the rhizosphere of soybean plants grown on Ultisol of Bengkulu. All replications receive 1 ton ha-1 of farmyard manure and all biofertilizer replication receives 20 kg ha-1 Urea, 20 kg ha-1 SP36 and 60 kg ha-1 KCl. Chemical fertilizer application (80 kg ha-1 Urea, 80 kg ha-1 SP36 and 60 kg ha-1 KCl) used as control. Research result showed that there was a specific combination between soybean variety with AMF and strains of rhizobia. Wilis will gave highest response if paired with Acaulospora sp – TEKR 6.29, Gl. etunicatum – KLKR 5.31, Gl. manihotis- KLKR; Pangrango with Acaulospora sp – TEKR 6.29, Gl. manihotis – KLKR 5.31; and Ceneng with Gi. margarita –TEKR 6.29, Gl. etunicatum- KLKR 5.31, Gl. etunicatum – TEKR 6.29, Gl. manihotis – KLKR 5.31, and Gl. manihotis – TEKR 6.29. Research result also showed that Ceneng gave more consistently response than two other varieties and suitable with every AMF and rhizobia strains tested.